Quality evaluation in schools incorporated in the National system of environmental certification from the Bio Bio provine (Chile) - Burgos Peredo, Oscar Eduardo; Perales Palacios, F. Javier; Gutiérrez Pérez, José (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This research attempts to evaluate the qual ity and impact of the implementation of the Environmental Education (EA) in schools that belong to the National System of Environmental Certification (NSEC) in Bio Bio province (Chile) as a comparison with ones that are not members in this certification. Throughout this research, it is performed a description of the program in different stages and a value of its implications and ability to promote sustainable changes in schools with impact in the territory, people and organizations of the environment. The research hypotheses expose that the environmental education has been incorporated efficiently to the teaching work, with a relevant participation in the precision of the Institutional Education Project (IEP) and consolidating an associative networking creation for the procedure in local environmental plans. After the research process based on the survey method were refuted the generality of the hypotheses.